The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jpn.12245
|View full text |Cite
|
Sign up to set email alerts
|

The fate of glycerol entering the rumen of dairy cows and sheep

Abstract: This study investigated the fate of glycerol entering the rumen, in particular whether glycerol could be absorbed across the rumen epithelium. Three non-lactating rumen-fistulated cows were used to calculate the overall disappearance rate of glycerol in vivo and evaluate the rate of ruminal glycerol absorption. Rumen epithelial tissues isolated from sheep were used to characterise glycerol transport properties. The rate of rumen microbial degradation of glycerol was then studied in an in vitro system under ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
(28 reference statements)
2
13
1
1
Order By: Relevance
“…High proportion of gluconeogenic precursors can escape microbial fermentation and degradation of the rumen and absorbed intact in the small intestine [42]. The rest of G is metabolized by rumen microbes mainly to propionate, butyrate, and acetate [8,43] whereas the rest of PG is mainly metabolized into propionate, propanol, and propanal [30].…”
Section: Discussionmentioning
confidence: 99%
“…High proportion of gluconeogenic precursors can escape microbial fermentation and degradation of the rumen and absorbed intact in the small intestine [42]. The rest of G is metabolized by rumen microbes mainly to propionate, butyrate, and acetate [8,43] whereas the rest of PG is mainly metabolized into propionate, propanol, and propanal [30].…”
Section: Discussionmentioning
confidence: 99%
“…Kristensen and Raun [ 27 ], when administering large amounts of glycerol (925 g/d), found that only 10% of this compound was found in the vena porta and the rest reached the liver as volatile fatty acids. Other studies show that glycerol can be absorbed from the rumen in significant amounts and its absorption mainly occurs by passive diffusion [ 28 ].…”
Section: Effect Of Glycerol On Rumen Processes and Metabolismmentioning
confidence: 99%
“…Lactic acidosis is reduced due to an increase in the population of lactate-consuming bacteria and undue fermentation [19]. As a consequence, some benefits are gained, such as rumen development and feed efficiency improvement [15,16].…”
Section: Ruminal Digestion and Fermentation Of Crude Glycerinmentioning
confidence: 99%
“…Because of its own fermentation profile, crude glycerin can avoid severe reduction of ruminal pH and the development of rumen acidosis. The larger portion of crude glycerin (∼43%) is rapidly absorbed by rumen papillae, whereas 25-45% are fermented to butyrate and propionate by alternative fermentative pathway (via succinate) and do not generate lactic acid, benefiting the rumen development and thus improving the feed efficiency [15,16,50].…”
Section: Crude Glycerin As a Strategy Ingredientmentioning
confidence: 99%
See 1 more Smart Citation